Advanced simulation methods for reliability analysis and updating of stochastic dynamic systems with applications to structural dynamics, seismic risk and loss assessment - Sahil Bansal (2015)
Given the fact that often low-probability extreme events can lead to disastrous consequences, the simulation and prior assessment of the civil engineering systems and critical infrastructure systems in such events are very important. To assess the system performance subjected to dynamic excitations realistically, stochastic system analyses considering all the important uncertainties including both aleatory and epistemic uncertainties, and modeling errors, which require a huge number of random variables, need to be performed. In this thesis, the focus is on the development of new stochastic simulation algorithms for Bayesian model updating, robust reliability (or its compliment "failure" probability) updating, extreme-event simulation and probability computation, conditional failure sample simulation, and their applications to the evaluation of reliability, seismic risk and loss assessment of civil engineering structures.